10.1k views
0 votes
Solve using the quadratic formula
2x^2+x+67=0

1 Answer

5 votes

Answer:


\displaystyle x=(-1 \pm i√(535))/(2)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Multiple Roots
  • Standard Form: ax² + bx + c = 0
  • Quadratic Formula:
    \displaystyle x=(-b \pm √(b^2-4ac))/(2a)

Algebra II

  • Imaginary Root i = √-1

Explanation:

Step 1: Define

Identify

2x² + x + 67 = 0

a = 2

b = 1

c = 67

Step 2: Solve for x

  1. Substitute in variables [Quadratic Formula]:
    \displaystyle x=(-1 \pm √(1^2-4(2)(67)))/(2(1))
  2. Multiply:
    \displaystyle x=(-1 \pm √(1^2-4(2)(67)))/(2)
  3. [√Radical] Evaluate exponents:
    \displaystyle x=(-1 \pm √(1-4(2)(67)))/(2)
  4. [√Radical] Multiply:
    \displaystyle x=(-1 \pm √(1-536))/(2)
  5. [√Radical] Subtract:
    \displaystyle x=(-1 \pm √(-535))/(2)
  6. [√Radical] Simplify:
    \displaystyle x=(-1 \pm i√(535))/(2)
User Bkkbrad
by
6.2k points